1997
DOI: 10.1080/87565649709540682
|View full text |Cite
|
Sign up to set email alerts
|

From first words to grammar in children with focal brain injury

Abstract: The effects of focal brain injury are investigated in the first stages of language development, during the passage from first words to grammar. Parent report and/or free speech data are reported for 53 infants and preschool children between 10 -44 months of age. All children had suffered a single, unilateral brain injury to the left or right hemisphere, incurred before six months of age (usually in the pre-or perinatal period). This is the period in which we should expect to see maximal plasticity, but it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(138 citation statements)
references
References 130 publications
11
124
3
Order By: Relevance
“…Such a lateralized effect supports the theory of early right-hemisphere involvement in language development [18] but stands in contrast to studies of phoneme discrimination, which have found early signs of left-greater-than-right asymmetries [1]. While left temporal brain structures are thought to be more involved in phonological decoding and phonological discrimination in both infants [1,19,20] and adults [15,21,22], it has been proposed that word-level recognition processes involve right-sided regions during the earliest stages of language acquisition [18,23,24].…”
Section: Vol 14 No 18 19 December 2003contrasting
confidence: 42%
“…Such a lateralized effect supports the theory of early right-hemisphere involvement in language development [18] but stands in contrast to studies of phoneme discrimination, which have found early signs of left-greater-than-right asymmetries [1]. While left temporal brain structures are thought to be more involved in phonological decoding and phonological discrimination in both infants [1,19,20] and adults [15,21,22], it has been proposed that word-level recognition processes involve right-sided regions during the earliest stages of language acquisition [18,23,24].…”
Section: Vol 14 No 18 19 December 2003contrasting
confidence: 42%
“…Although the lesion-symptom correlations that we observe do not always match the correlations observed in adults, they may provide insights into the initial conditions that lead to left-hemisphere specialization for language under normal conditions (Bates et al, 1997;Reilly et al, 1998;Thal et al, 1991;Vicari et al, 2000). For example, we find that early delays in word comprehension and symbolic gesture are actually somewhat more common in children with RHD, but this bias has only been observed in our laboratories in the period between 10 and 20 months of age.…”
Section: Discussionmentioning
confidence: 61%
“…Even more surprising from the point of view of adult aphasia, it has proven extremely difficult to demonstrate significant differences in language outcomes between children with left-hemisphere damage (LHD) vs right-hemisphere damage (RHD). Although some differences have been reported during the period in which language is first acquired (Bates et al, 1997;Reilly, Bates, & Marchman, 1998;Thal et al, 1991;Vicari et al, 2000), the vast majority of studies have failed to uncover robust and statistically reliable left/right differences in children who are tested beyond 5-7 years of age. To be sure, a few studies have reported subtle differences between LHD children and their controls, differences that are not observed (or occur in a less specific form) when RHD children are compared to their own, separate group of controls Aram, Ekelman, Rose, & Whitaker, 1985;Ballantyne, Scarvie, & Trauner, 1994-but see Ballantyne & Trauner, 1999;Dennis & Whitaker, 1976Riva, Cazzaniga, Pantaleoni, Milani, & Fedrizzi, 1986).…”
mentioning
confidence: 99%
“…Language development is also arguably one of the most rapid aspects of development, and shows great variability between children (Bates, Dale, & Thal, 1995;Fenson et al, 2000;Fenson, Dale, Reznick, & Bates, 1994), as well as being sensitive to a number of negative factors that are more common in this setting, including HIV infection, cerebral malaria, meningitis, and other causes of brain injury and dysfunction (Baker, Kummer, Schultz, & Ho, 1996;Bates et al, 1997;Brouwers et al, 2001;Davis et al, 1997;McNeilly, 2005;Wolters, Brouwers, Civitello, & Moss, 1997). Its study therefore has become in recent years an essential part of studies of child development outcomes following exposures and interventions in the prenatal period and infancy (A. Abubakar, Van Baar, Prado et al, 2010;Stoltzfus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%